Dampak Game Online Terhadap Kreativitas Belajar Anak di Sekolah Dasar - Innayah, Hanifah (TAZKIA JURNAL, 2024)
During this time, online games tend to be considered negative because of the many children who ditch school due to excessive online gaming. However, actually online games also have a positive side. Online games can train the brain to get used to thinking creatively. This study aims to determine the relationship of online games with the children’s learning creativity at SDN Mojorayung 01, Kabupaten Madiun in the schooling year of 2024/2025. This study uses quantitative methods with a correlational expo facto design. The population of this study were all students of class III-VI at SDN Mojorayung 01 Kabupaten Madiun in the schooling year of 2024/2025 which totaled 161 students. The sampling technique used in this study was purposive sampling technique, namely students who often play online games. Thus the sample in this study amounted to 57 students. Data collection techniques in this study use questionnaires. The data analysis technique used is the Product Moment correlation analysis technique with the prerequisite test, which includes the normality and linearity test followed by a significance test. The conclusions of this study are: there is a significant relationship between online games with the creativity of children's learning in Mojorayung 01 Elementary School, Madiun in the schooling year of 2024/2025. Children who often play online games will be more creative, the more unyielding, the more different they think than usual.